Positioning of entrepreneurial systems of the organic products production in the conditions of globalization and innovative economics: managerial aspect - Varaksina, Elena; Вараксіна, Олена; Savenko, Olena; Савенко, Олена Анатоліївна; Nihmatova, Olena; Нігматова, Олена; Skrypnyk, Viktoriia; Скрипник, Вікторія; Kolesnyk, Tetiana; Колесник, Тетяна; Ivanova, Tamara; Іванова, Тамара; et al. (Консультаційно-навчальний центр КЕЙ, 2022)
The production of organic products meets modern standards of economic, social and environmental sustainability. Demand for organic products is growing worldwide as consumers perceive it as providing a healthy diet and protecting the environment. However, there is a low level of awareness of the organic products benefits in developing countries, including Ukraine. Therefore, organic producers need to create an attractive image for “organic” among consumers, teach them to distinguish relevant products from products with other eco-labels, position such products, taking into account the hierarchy (importance) of motives for its consumption among the target audience. At the same time, it is important to maintain consistency in determining the characteristics of organic products in the consumer market. Under these conditions, it is important to implement organic business brand communications in social networks that broadcast the values of organic products to consumers through appropriate marketing (text) messages on a regular basis. Therefore, the aim of this study is to analyze the positioning of producers of the organic market of Ukraine on the social network Facebook, which is the most attractive to the Ukrainian audience. The study fills the lack of information on the level of activity of organic producers in social media, reveals the content of the communication process with consumers and establishes its correlation with the main factors of consumption of organic products. Based on critical analysis and generalization of scientific works, sociological studies of motives for buying organic products in Ukraine and practical recommendations for positioning organic products on social networks, the main factors motivating consumers to choose organic products were identified. The obtained results were compared with the main topics of marketing messages of organic producers. The research group included 5 leading Ukrainian organic producers, namely Organic Milk TOV, StaryiPorytsk TOV, Haleks-Agro PE, EthnoProduct PrJSC and Malyshko FOP. The materials of the study were marketing (text) messages contained on the official pages of certified producers of organic products on the social network Facebook, created by marketers to communicate, engage and inform consumers about the availability, benefits or any other information about producers. Marketing (text) messages were collected for the period from February 31, 2018 to February 31, 2021 (or 3 years). For the first time, corpus linguistics tools were used in the article (with the help of the AntConс text analysis computer program) to study the content of marketing (text) messages contained on the official pages of organic producers on the social network Facebook. Corpus linguistics allowed to identify objective, quantitative relationships between words that are often found in marketing messages, and to interpret the results based on the selection of the main topics that guide organic producers in the process of positioning organic products. In addition, it was established whether there is a problem of disagreement in the understanding of term “organic” among organic producers operating in the market. It was found that not all studied organic producers adhere to the optimal recommended frequency of publications per month to maintain regular communication with the target audience. Only 1 in 5 companies surveyed systematically to maintain this connection, which means that business owners consider it important to have a page, but they do not communicate with consumers on a regular basis. Companies use for their positioning on the social network Facebook such elements as: products, their taste, quality, health benefits, national and territorial affiliation of production, land protection, animal welfare, characteristics of the place of production. None of the producers attracts the full range of factors that motivate consumers to buy organic products, but there is a focus on selfish motives. Producers have different ideas about the essence of “organic”. Some point more to the name of their own products and nationality, ignoring the properties of organic products and the way they are produced. This gives reason to talk about the lack of a systematic approach to the formation of the content of messages about organic products. Based on the multifaceted factors of consumption of organic products, there were arguments for some producers to pay more attention to the environmental component of production of such products. There is a need to highlight in text messages the altruistic values of organic products for consumers. To harmonize the positioning, you need to pay more attention to the taste of the product. However, one should also not forget about the nationality of production. Producers should pay attention to the positioning of the appearance of organic products. The value of organic products is a complex category, so for different groups of consumers there may be different determining motives for buying it. Виробництво органічної продукції відповідає сучасному стандарту економічній, соціальній та екологічній стійкісті. Попит на органічні продукти зростає в усьому світі, оскільки споживачі сприймають це як забезпечення здорового харчування та захист навколишнього середовища. Однак існує низький рівень обізнаності про органічні продукти переваги в країнах, що розвиваються, включно з Україною. Тому органічні виробники повинні створити привабливий імідж «органіки» серед споживачів, навчити їх відрізняти релевантну продукцію від продукції з іншими екомаркуваннями, позиціонувати таку продукцію, враховуючи ієрархію (важливість) мотивів її споживання серед цільової аудиторії. Водночас важливо підтримувати послідовність у визначенні характеристики органічної продукції на споживчому ринку. За цих умов важливо впроваджувати комунікації бренди органічного бізнесу в соціальних мережах, які транслюють цінності органічних продуктів споживачам через відповідні маркетингові (текстові) повідомлення на регулярній основі. Тому метою цього дослідження є аналіз позиціонування виробників органічного ринку України в соціальній мережі Facebook, яка є найбільш привабливою для української аудиторії. Дослідження заповнює дефіцит інформації про рівень активності органічних виробників у соціальних мережах, розкриває зміст комунікаційного процесу зі споживачами та встановлює його кореляцію з основними факторами споживання органічних продуктів.
Позиціонування підприємницьких систем виробництва органічної продукції в умовах глобалізації та інноваційної економіки: управлінський аспект
Keywords: Organic products; органічні продукти; Environmental sustainability; екологічна стійкість; Healthy diet; здорове харчування; Consumer market; споживчий ринок